STUDY ON THE SURFACE MODIFICATION OF SILICA NANOPARTICLE QUANTUM DOTS (SINP@QDS) FOR E COLI BACTERIA DETECTION - Ayu Widyasari, Diaz
The presence of E. coli bacteria is considered as a biological indicator of water pollution hence the management of water quality is necessary . Bacterial detection methods currently rely on laboratory-based techniques with limited application,. Biosensors can provide rapid, sensitive and selective detection of the presence and number of bacteria in various environments. In this research, biosensors were made using natural silica precursors combined with quantum dots as optical transducers. Natural silica was synthesized into silica nanoparticles through the sol-gel method and then the surface was modified to incorporate the quantum dots and bind to the bioreceptors, E. coli antibodies. Based on the results of surface area analysis using the Brunauer-Emmett-teller (BET) method, the surface area of silica nanoparticles (SiNP) obtained was 137.75 m2/g with a particle size of 43.5 nm. The results of X-Ray Diffraction (XRD) analysis showed that the formed nanoparticles had an amorphous phase. The surface of the SiNP was then surface modified using 2 different methods, which are silanization using using 3-Aminopropyl Triethoxysilane (APT) and hydrosilylation using undecylenic acid to understand which method was more effective for the synthesis of SiNP@QD. In this study, there are 2 types of quantum dots used, carboxyl CdSe and amine CdSe. The addition of quantum dots in each method was carried out with using EDC and NHS as activators. Furthermore, SiNP@QD was immobilized with bioreceptors, E. coli antibody and Fourier Transform Infra-Red (FTIR) analysis was carried out to prove that the covalent bond between the surface of silica nanoparticles and E. coli antibody. Finally, the detection application was carried out using a fluorescence spectrophotometer at an excitation wavelength of 360 nm and an emission wavelength of 400-800 nm. The peak intensity of SiNP@QD was at a wavelength of 565 nm, and the peak intensity for detection of E. coli bacteria with the addition of SiNP@QD appeared at a wavelength of 435 nm and 565 nm. Detection tests were carried out with variations in incubation time and variations in the concentration of E. coli bacteria. The most optimal incubation time was 15 minutes with an intensity of 84.23 a.u. at a wavelength of 435 nm. Limit of Detection SiNP@QD is calculated at the maximum emission peak at wavelength of 435 nm, where a LoD value of 1.6 CFU/mL is obtained.